PERANAN KOMPETENSI KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA TERNAK SAPI DIDESA BUNE KAB. BONE SULAWESI SELATAN - Saleh, Haeruddin (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Bone regency is one of the largest cattle producing areas in South Sulawesi but still in traditional management. So it needs to be done a breakthrough that is improving entrepreneurial competence in the livestock business. This study aims to examine, analyze and interpret the implementation of assistance in improving the competence of entrepreneurship. The type of this research is eksplanatory, while the respondent is a cattle rancher who uses a sample of 30 people. The results of research processed and described that shows that the increased entrepreneurial competence can provide knowledge to farmers. The entrepreneurial competence consisting of technical competence that includes the development of livestock germs, nutrition and feeding, improvement of reproduction process and comfort of livestock, and managerial competence include; business planning, labor management, marketing and financial management. With the increasing of entrepreneurship competence give effect to the success of cattle business, that is increasing of productivity, increasing of livestock ownership and increasing of breeder's income.